1999
DOI: 10.1073/pnas.96.18.10080
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis by adenovirus E4orf4 protein is specific to transformed cells and requires an interaction with protein phosphatase 2A

Abstract: We previously have shown that adenovirus type 5 E4orf4 protein associates with protein phosphatase 2A (PP2A) and induces apoptosis in transformed cells in a p53-independent manner. Here we show that the interaction between E4orf4 and PP2A is required for induction of apoptosis by the viral protein. This conclusion is supported by a mutation analysis of E4orf4 protein, showing a correlation between the ability to bind PP2A and to induce apoptosis, and by the observation that transfection of an antisense constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
193
0
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(205 citation statements)
references
References 36 publications
8
193
0
4
Order By: Relevance
“…Even though these viruses are not otherwise related, they all seem to have adapted a similar strategy to affect cellular processes by direct interaction with PP2A. Similar to the Vpr effects, both adenoviral E4orf4 [63][64][65] and HTLV Tax protein induce cell cycle G2 arrest [59]. These two viral proteins both bind to PP2A and affect its enzymatic activity [63,66].…”
Section: Potential Role Of Pp2a In Cell Cycle G2/m Regulation During mentioning
confidence: 99%
“…Even though these viruses are not otherwise related, they all seem to have adapted a similar strategy to affect cellular processes by direct interaction with PP2A. Similar to the Vpr effects, both adenoviral E4orf4 [63][64][65] and HTLV Tax protein induce cell cycle G2 arrest [59]. These two viral proteins both bind to PP2A and affect its enzymatic activity [63,66].…”
Section: Potential Role Of Pp2a In Cell Cycle G2/m Regulation During mentioning
confidence: 99%
“…Another viral protein that interacts with PP2A is adenovirus E4orf4. By binding the B subunit in the holoenzyme, E4orf4 induces p53-independent apoptosis (Kleinberger and Shenk, 1993;Marcellus et al, 2000;Shtrichman et al, 1999Shtrichman et al, , 2000. PP2A also associates with numerous cellular proteins that are involved in growth regulation Virshup, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It down-regulates expression of genes that have been activated by E1A and cAMP (16,17), induces hypophosphorylation of various viral and cellular proteins (16,18), regulates alternative splicing of adenovirus mRNAs (18), and induces p53-independent apoptosis in transformed cells (19 -21). E4orf4-induced apoptosis is specific to transformed cells (22), and thus E4orf4 may have a therapeutic potential for cancer.…”
mentioning
confidence: 99%
“…We, and others, have recently shown that the interaction with PP2A complexes that include the B␣/B55, but not the BЈ/B56 subunit, is required for induction of apoptosis by E4orf4 (22)(23)(24). Binding the B subunit alone is not sufficient for induction of apoptosis, because an E4orf4 mutant, A3 (S95P), could bind the B subunit, whereas the A and C subunits were excluded from the complex, causing A3 to act as a dominant negative mutant (23).…”
mentioning
confidence: 99%